Tracking the future path of HIV prevalence among individuals aged 15-49 years in Sierra Leone using Holt’s linear method - Dr. Smartson. P. NYONI; Thabani NYONI (Zien Journals, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Sierra Leone from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will remain constant at around 1.5% throughout the out of sample period. Therefore, we encourage authorities to scale up HIV diagnosis, prevention and treatment especially among key populations.
Keywords: Exponential smoothing; Forecasting; HIV prevalence